2017
DOI: 10.1038/ncomms15730
|View full text |Cite
|
Sign up to set email alerts
|

Misfolded polypeptides are selectively recognized and transported toward aggresomes by a CED complex

Abstract: Misfolded polypeptides are rapidly cleared from cells via the ubiquitin–proteasome system (UPS). However, when the UPS is impaired, misfolded polypeptides form small cytoplasmic aggregates, which are sequestered into an aggresome and ultimately degraded by aggrephagy. Despite the relevance of the aggresome to neurodegenerative proteinopathies, the molecular mechanisms underlying aggresome formation remain unclear. Here we show that the CTIF–eEF1A1–DCTN1 (CED) complex functions in the surveillance of either pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(63 citation statements)
references
References 67 publications
4
59
0
Order By: Relevance
“…In summary, in this section we tested the effect of different pharmacological perturbations. We also confirmed here that the expression of the labelled tracer (Synphilin1) is not the main driving force for clustering, consistent with the previous characterization that the tracer labels aggregates that are mostly composed of misfolded polypeptides (JA, 2006; Meriin et al, 2012; Park et al, 2017; Tanaka et al, 2004). We find that the theoretical model holds robustly under different drug treatments that globally affect protein quality control: a drug that reduces global protein synthesis, thereby reducing the concentration of misfolded polypeptides is found to reduce super-saturation (i.e.…”
Section: Resultssupporting
confidence: 91%
“…In summary, in this section we tested the effect of different pharmacological perturbations. We also confirmed here that the expression of the labelled tracer (Synphilin1) is not the main driving force for clustering, consistent with the previous characterization that the tracer labels aggregates that are mostly composed of misfolded polypeptides (JA, 2006; Meriin et al, 2012; Park et al, 2017; Tanaka et al, 2004). We find that the theoretical model holds robustly under different drug treatments that globally affect protein quality control: a drug that reduces global protein synthesis, thereby reducing the concentration of misfolded polypeptides is found to reduce super-saturation (i.e.…”
Section: Resultssupporting
confidence: 91%
“…Mass spectrometry analysis revealed that the ubiquitin molecules are expressed from the UBC (polyubiquitine C) locus (Supplemental Figure 9). In addition, recent studies have shown that the eukaryotic translation elongation factor 1α (eEF1α) forms a CTIF-eEF1A1-DCTN1 complex to facilitate the aggresomal targeting of misfolded polypeptides (Park et al , 2017). We found that the levels of eEF1α in Ant1-overexpressing cells are unchanged in RIPA (1% Triton X-100, 0.1% SDS)-extracted, and slightly increased in SDS/urea (5% SDS, 8 M urea) -extracted cell lysates (Figure 7C).…”
Section: Resultsmentioning
confidence: 99%
“…HeLa cells were grown in DMEM supplemented with 10% (v/v) fetal bovine serum and 1% (v/v) penicillin/streptomycin solution (all from GE Healthcare Korea, Seoul, South Korea). The cells were transiently transfected with the plasmids or 100 mM final synthetic siRNAs (GenePharma, Shanghai, China) by using Lipofectamine 2000 (Thermo Fisher Scientific) or Oligofectamine (Thermo Fisher Scientific), respectively (29)(30)(31)(32). Total-cell RNA and protein were prepared as previously described (28,33).…”
Section: Cell Culture and Transfectionmentioning
confidence: 99%
“…Polysome fractionations with cytoplasmic extracts of cells (three 150-mm culture dishes per sample) were performed as previously described (29,32,33). Before harvesting, the cells were either nonirradiated or irradiated with UVC (25 J/m 2 ) and incubated for 2 h. Total-cell RNAs were purified from each fraction and subjected to qRT-PCR.…”
Section: Polysome Fractionationmentioning
confidence: 99%